Mycorrhizal infection and foliar phosphorus content of seedlings of three dipterocarp species growing in a selectively logged forest and a forest plantation - Lee, S.S.; Lim, K.L. (Kluwer Academic Publishers, 1989)
Foliar phosphorus content and mycorrhizal infection of dipterocarp seedlings growing in a 61-year-old forest plantation (site A) and a selectively logged forest (site B) were determined. Mycorrhizal infection levels were high-83.7% for Shorea bracteolata and 95.0% for S. leprosula at site A, and 77.8% for S. leprosula and 86.3% for S. curtisii at site B. The seedlings all had similar foliar phosphorus contents although available soil phosphorus at site B was half that at site A. Significant correlations were obtained between foliar phosphorus content and percentage mycorrhizal infection at site B only. © 1989 Kluwer Academic Publishers.